BAG3 in human tumors - Manzo, Paola; Cammarota, Anna Lisa; Dimitrov, Jelena; Falco, Antonia; Rosati, Alessandra; Marzullo, Liberato; Turco, Maria Caterina; De Laurenzi, Vincenzo; Sala, Gianluca; De Marco, Margot; Basile, Anna (Frontiers in Oncology, 2025)
Previous studies identified BAG3 as a stress-induced protein with pro-survival functions in various tumors. Based on this assumption, we analyzed the expression and secretion of BAG3 in 24 cancer cell lines representing ten types of cancer and compared these results with samples from primary tumors. BAG3 was ubiquitously expressed and secreted by all cell lines. Serum levels of BAG3 were significantly elevated in patients with liver, pancreatic, and ovarian cancers versus healthy controls. Immunohistochemical analysis confirmed widespread high BAG3 expression across multiple tumor types, often correlating with tumor grade. These data support BAG3 as a key regulator of tumor survival and a promising biomarker and therapeutic target.